Artificial Intelligence for Human Life: A Critical Opinion from Medical Bioethics Perspective – Part II - Khairatun Hisan, Urfa; Miftahul Amri, Muhammad (Journal of Public Health Sciences, 2022)
Healthcare and medical fields are among the areas of AI applications that require serious attention when it comes to ethical and trustworthy AI. In the medical field, artificial intelligence is applied in laboratory research, regulation-policy making, and clinical intervention. Several factors need to be seriously accounted for in the AI-empowered healthcare system, including algorithm transparency, bias mitigation, domain-expert involvement, privacy and data protection, and informed consent. In this article, we summarized the applications of AI in the field of medical and healthcare sectors. We also presented the possible ethical issues in AI applications in mentioned sectors. These issues include transparency and safety, informed consent and right to information, algorithmic fairness and biases, and data privacy and sharing regulation. We then present the basic principles of AI ethics and the existing AI guidelines, especially for the fields of medicine and healthcare. Based on the existing issues and guidelines, we believe that there are still many factors that need to be perfected, such as how we can generalize these guidelines worldwide and how these guidelines can be legally-binding. Detailed clauses in the guideline and law enforcement are another issue that should be addressed such that no loophole can be addressed. Ethical consideration is critical in AI applications, especially in the medical and healthcare fields. Until these issues can be totally addressed, we believe that AI applications in healthcare should be very strictly monitored.